THE EFFECT OF MOTIVATION ON PURCHASING INTENTION OF ONLINE GAMES AND VIRTUAL ITEMS PROVIDED BY ONLINE GAME PROVIDER - Sisca Stefany (CommIT (Communication and Information Technology) Journal, 2014)
The development of online games is so high that leads many companies to compose games. To increase competitiveness, extra service is needed for the customers. Before giving service, online games provider has to know what factor that motivates player to buy online games and virtual items that are presented in order to increase competitiveness. The research is done by using case of online games perfect world, where the area of respondents is Jakarta and the age ranges between 15 to 24. This research involves survey for 186 respondents in which 30 respondents are for pilot test while 156 are for actual test. The data processing is used SEM which the measurement variables consist of effort expectancy, performance expectancy, perceived value, enjoyment story, enjoyment length, enjoyment graphic, enjoyment control, customization, purchase intention and actual purchase behavior. The result of research shows that motivation factor that has high effect to purchase intention is perceived value, enjoyment story, enjoyment length, enjoyment control and customization. While, purchase intention affects actual purchase behavior significantly